Legionella contamination in the water system of hospital dental settings - Veronesi, L.; Capobianco, E.; Affanni, et al., P. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim of the work: Among hospital facilities the dental unit is an environment that is at major risk of Legionella due to equipment such as the air/water syringe, the turbine, the micromotor and the scaler which generate potentially harmful aerosols that may to be a source of exposure to Legionella spp. particularly in immunodeficient patients, and those affected by chronic diseases, and also in dental personnel. Therefore, an examination of the extent of Legionella spp. contamination in the dental chairs waterlines and the incoming water supply of some public dental units is the subject of the present study. Methods: From February 2002 to March 2004, a total of 208 water samples were collected: 160 samples from the water supply of 4 dental chair and 48 samples from the cold incoming tap water of 2 units. Results: Legionella spp. was detected in 46 samples (22.1% ): 19 of them (41.3% of Legionella spp.; 9.1% of the total) were Legionella pneumophila; Pseudomonas aeruginosa was detected in 86 samples (41.4%) and both microorganisms were detected in 2 samples (0.96%). Conclusions:Our results show a microbiological condition in dental settings, that is not at all satisfactory due to the presence of Legionella in concentrations that are considered to be a health hazard (≥103) in certain cases. Given the extent of the health risk in these surroundings, the difficulty in its assessment, and also considering the wide diffusion of general dental care, our investigation has confirmed the need to regularly monitor the microbiological condition of water in dental units